PENGENALAN IDENTITAS BUDAYA BETAWI MELALUI ADAPTASI CERITA ANAK NARADA KARYA KAMIL KAILANI - Fenny Rahma Dania; Zamzam Nurhuda; Darsita Suparno; Ulil Abshar; Achmad Satori; Mauidlotun Nisa' (STIQ Amuntai, 2023)
The objectives of this study are classified into four categories, namely: 1) analyzing the process of adaptation of Arabic to the Betawi language by identifying linguistic, cultural, and contextual changes that occur using adaptation methods; 2) identifying changes in the cultural context to uncover aspects such as traditions, values, and social norms reflected in the story; 3) analyze the use of Arabic vocabulary and phrases in this story as a result of adaptation. This method helps to understand the role of Arabic vocabulary in the story and its influence on the Betawi language; 4) examine the cultural and social impact of translation using the Story Adaptation method; 5) evaluate the cultural and social impact of adapting this story in Betawi society. The analysis results show that children's stories can influence cultural identity and enrich Betawi cultural heritage. This study used qualitative-descriptive research methods. The research method uses two sources, namely, primary from children's storybooks